Molecular characterization and resistance mechanisms of ertapenem-non-susceptible carbapenem-resistant Klebsiella pneumoniae co-harboring ESBLs or AmpC enzymes with porin loss or efflux pump overexpression - Su, Yingying; Zou, Guangmei; Huang, Xin; Bi, Jinli; Meng, Liqin; Zhao, Wei; Li, Taijie (Journal of bacteriology, 2025)
This study highlights the complex, multifactorial nature of carbapenem resistance in carbapenem-resistant Klebsiella pneumoniae (CRKP), involving enzyme-mediated resistance, reduced membrane porin expression, and overactive efflux pumps. These findings provide valuable insights into CRKP resistance mechanisms and can aid in controlling CRKP in China.